Evaluating Acceleration of Stunting Prevention in Indonesia (2018-2024): A Roadmap-Based Program Analysis - Alfi Rusdianti; Suparji Suparji; Heru Santoso Wahito Nugroho; Budi Joko Santosa; Sunarto Sunarto (Health Dynamics, 2025)
Indonesia’s 2018-2024 National Roadmap for Stunting Prevention aims to reduce stunting prevalence to 14% by 2024 through multisectoral interventions. This commentary evaluates the program’s acceleration, identifying systemic gaps in implementation despite robust policy frameworks. Using qualitative analysis of government reports, field studies, and secondary data, we assess progress against key roadmap indicators, including nutrition-specific interventions, community empowerment, and interagency coordination. Findings reveal persistent challenges: fragmented coordination between national and local agencies, uneven funding distribution favoring urban centers, and inadequate real-time monitoring systems. Case studies from regions like Lombok (successful integrated nutrition campaigns) and Papua (persistent access barriers to clean water and healthcare) illustrate disparities in program effectiveness. Additionally, socio-cultural factors, such as low parental awareness of nutrition, further hinder progress. We argue that accelerating stunting reduction requires strengthening decentralized governance, prioritizing budget equity for rural areas, and leveraging digital tools for data integration. Community-driven education initiatives, supported by local leaders, are critical to shifting health behaviors. Without addressing these structural and operational bottlenecks, Indonesia risks missing its 2024 target, undermining broader Sustainable Development Goals (SDGs) linked to child health and equity. This analysis urges policymakers to adopt adaptive, evidence-based strategies to transform roadmap commitments into actionable outcomes.